LEADING WORKPLACE SAFETY. (7th October 2012) - Ellis, C
Abstract : Leading workplace safety demands a different approach from most other business functions. Safety performance relies on minute by minute decisions by individuals in a workforce. A moment of distraction may cause an incremental reduction in productivity, but that same inattention has the potential to cause a serious workplace injury or fatality. While the individual drivers of workplace safety behaviour are complex many businesses have been successful by addressing safety culture as a whole. Workplace health and safety must be led as well as managed. Today most leaders of large businesses recognise the engagement, productivity and cost benefits from actively leading workplace health and safety. The challenge is that while they have a desire to improve workplace health and safety, many business leaders are uncertain what their role is and where their effort will be most effective. The Business Leaders Health and Safety Forum brings together leaders of over 100 of New Zealand's largest companies with the vision of Zero Harm Workplaces. Members acknowledge that they are in a unique position to improve workplace health and safety in their own businesses and across the wider business community. The goal is to lead a step change in health and safety performance over the next 2 years by: developing and growing world-class safety leadership in New Zealands business leaders using the individual and collective influence of business leaders to positively contribute to changes in health and safety in New Zealand providing opportunities for business leaders to share resources to overcome common challenges.